Hyphocapnodia sichuanensis gen. et sp. nov. (Capnodiaceae), a novel hyphomycete from Sichuan Province, China - Lu, Zheng-Hua; Wanasinghe, Dhanushka N.; Madrid, Hugo; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2022)
A hyphomycetous sooty mould was collected on a dead bamboo (Bambusoideae, Gramineae) from a terrestrial habitat in Sichuan Province, China. To establish the phylogenetic position of newly collected sooty mould within the Capnodiales, we sequenced two rDNA regions, ITS1-5.8S-ITS2 (ITS) and 28S, and two protein-coding genes tef1-α and rpb2. Based on maximum likelihood and Bayesian analyses of a combined dataset and an examination of morphology, we describe and illustrate Hyphocapnodia gen. et sp. nov. Hyphocapnodia sichuanensis is characterized by subcylindrical, dark brown to black synnemata with monoblastic conidiogenous cells producing subcylindrical to fusiform, transversely septate, brown conidia with a truncate base.